Double-lithium-salt asymmetric structure solid electrolyte as well as preparation method and application thereof
By adopting the preparation method of asymmetric structure of double lithium salt, the problems of poor interface stability and narrow electrochemical window of solid lithium metal batteries are solved, and higher energy density and better battery safety are achieved.
Patent Information
- Application Number
- CN202411576466.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
The poor interface stability and narrow electrochemical window of solid-state lithium metal batteries lead to safety hazards and insufficient energy density in the battery under extreme conditions.
The preparation method of asymmetric structure solid electrolyte of bilithium salt is adopted. By combining PVDF-HFP, LiFSI and LiDFOB with LATP inorganic fillers, a double-layer structure electrolyte is constructed, and the electrolyte membrane is prepared by two-step casting method to improve the interface stability of the electrolyte and electrochemical properties.
It significantly improves the interface stability and electrochemical performance of solid-state lithium metal batteries, broadens the electrochemical window, improves ion conductivity and lithium ion migration number, and enables the battery to operate stably within a wider voltage range, achieving rapid charging and discharging. , and improves the cycle stability and safety of the battery.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a double lithium salt asymmetric structure solid electrolyte and a preparation method and application thereof. Background Art
[0002] With the sharp increase in global energy consumption and the increasingly serious environmental pollution problem, the rapid development of new energy technologies has become the focus of widespread international attention. In this context, lithium-ion batteries have stood out among many energy storage technologies with their significant advantages such as high energy density, long cycle life and relatively low maintenance costs, especially in the field of new energy vehicles, showing great application potential. The popularization of new energy vehicles not only helps to reduce dependence on fossil fuels, but also effectively reduces greenhouse gas emissions, which is of great significance for promoting the transformation of the global energy structure and achieving sustainable development goals. However, the current traditional lithium-ion batteries with graphite as the negative electrode material have gradually approached their theoretical limit in terms of energy density, which is about 300 Wh / kg. This bottleneck limits their further development and application. In addition, traditional lithium-ion batteries have safety hazards under extreme conditions such as overcharging and short circuit, which has also aroused the industry's deep concern about battery safety. In order to break through this dilemma, researchers are actively exploring new battery technologies, among which solid-state lithium metal batteries (SSLMBs) are regarded as very promising candidates. Compared with traditional lithium-ion batteries, solid-state lithium metal batteries use solid electrolytes instead of liquid electrolytes, which is not only expected to significantly increase energy density, but also fundamentally solve safety hazards such as battery leakage and short circuits, thereby significantly improving the overall performance and safety of the battery. Therefore, the research and development of solid-state lithium metal batteries is regarded as a key link in promoting the innovation of new energy technologies and promoting the sustainable development of the new energy vehicle industry. It is attracting more and more scientific research forces and capital investment, in order to play a more important role in the future energy field.
[0003] Composite solid electrolytes (CSEs) inherit the advantages of inorganic ceramic electrolytes and organic polymer electrolytes and are considered to be one of the most promising candidates for future solid-state lithium metal batteries. Among the existing polymers, poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) has the advantages of easy processing, low crystallinity, and high dielectric constant, which can effectively improve the electrochemical performance of SSLMBs; NASICON-type inorganic ceramic particles Li1.3Al0.3Ti1.7(PO4)3 (LATP) have high ionic conductivity and a wide electrochemical window. However, its rigid characteristics and incompatibility with the lithium metal interface limit its development potential in practical applications.
[0004] Solving the interface problem of solid-state lithium metal batteries is of great significance to improving the energy density of batteries. For the anode | electrolyte interface, the uncontrollable growth of lithium dendrites causes the battery to short-circuit, which in turn causes safety accidents. On the cathode side, the narrow electrochemical window means that the electrolyte is easily oxidized and decomposed at a higher voltage, which can cause side reactions between the electrolyte and the cathode material, produce interface byproducts, and then lead to poor stability of the cathode | electrolyte interface. Summary of the invention
[0005] The purpose of the present invention is to provide a double lithium salt asymmetric structure solid electrolyte and its preparation method and application, so as to solve the technical problems of poor interface stability and narrow electrochemical window of solid electrolyte.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a double lithium salt asymmetric structure solid electrolyte, comprising the following steps: Dissolving PVDF-HFP, LiFSI and LiDFOB in a solvent to obtain a mixed solution; Dispersing LATP inorganic fillers in the mixed solution respectively to obtain two LATP precursor solutions with different concentrations; Two LATP layer precursor solutions with different concentrations were prepared by a two-step tape casting method to obtain a double lithium salt asymmetric structure solid electrolyte.
[0007] Furthermore, the usage ratio of the PVDF-HFP, LiFSI, LiDFOB and solvent is 3 g:1 g:(0.25~1) g:15 mL.
[0008] Furthermore, the solvent is N,N-dimethylformamide.
[0009] Furthermore, the concentrations of the two LATP precursor solutions of different concentrations are respectively a high-concentration LATP precursor solution and a low-concentration LATP precursor solution; The concentration of the high-concentration LATP precursor solution is 30 wt %, and the concentration of the low-concentration LATP precursor solution is 15 wt %.
[0010] Furthermore, the preparation process of the double lithium salt asymmetric structure solid electrolyte is specifically as follows: A low-concentration LATP precursor solution is first cast on a substrate, coated with a scraper, and then dried. A high-concentration LATP precursor solution is then cast, coated with a scraper, and then dried to obtain a double lithium salt asymmetric structure solid electrolyte.
[0011] Furthermore, when the scraper is applied to a small concentration LATP precursor solution, the thickness of the scraper is 220 μm; When the scraper is used to scrape a high-concentration LATP precursor solution, the thickness of the scraper is 250 μm; The substrate is a glass plate.
[0012] Furthermore, the temperature for drying the small concentration LATP precursor solution after scraping is 55°C and the time is 12 to 24 h.
[0013] Furthermore, the high concentration LATP precursor solution after scraping is dried at a temperature of 55°C for a period of 12 to 24 hours.
[0014] The invention also discloses a solid electrolyte with asymmetric structure of double lithium salt prepared by the preparation method.
[0015] The invention also discloses the application of the above-mentioned double lithium salt asymmetric structure solid electrolyte in a solid-state lithium metal battery.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a double lithium salt asymmetric structure solid electrolyte. By adopting PVDF-HFP as a polymer matrix, combining LATP inorganic filler with high ionic conductivity, and introducing two lithium salt additives, a double-layer structure is constructed, so that the electrolyte has enhanced interface stability on the cathode side, and reduces the reaction with lithium metal on the anode side, thereby improving the overall electrochemical performance, and effectively solving the problems of poor interface stability and narrow electrochemical window of traditional solid electrolytes in lithium metal batteries.
[0017] Furthermore, by optimizing the lithium salt ratio, the electrochemical window of the electrolyte is significantly broadened, and the ionic conductivity and lithium ion migration number are greatly improved, so that the battery can operate stably in a wider voltage range, achieve rapid charge and discharge, and improve the cycle stability and safety of the battery. These advantages make this patented technology have significant application potential in the field of high energy density and high safety solid-state lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a performance comparison data chart of different electrolytes; Among them: a-LSV curves of different solid electrolytes; b-CCD curves of single lithium salt and double lithium salt asymmetric structure solid electrolytes; c-impedance Nyquist diagram of single lithium salt and double lithium salt asymmetric structure solid electrolytes.
[0019] Figure 2The surface and cross-sectional morphologies of the double lithium salt asymmetric structure solid electrolyte prepared in Example 1 and the single lithium salt asymmetric structure solid electrolyte prepared in Comparative Example 1; Among them: a-single lithium salt asymmetric structure solid electrolyte; b-double lithium salt asymmetric structure solid electrolyte; Figure 3 The lithium ion migration numbers of the double lithium salt asymmetric structure solid electrolyte prepared in Example 1 and the single lithium salt asymmetric structure solid electrolyte prepared in Comparative Example 1; Figure 4 The limiting current density curve and lithium deposition|stripping curve of the double lithium salt asymmetric structure solid electrolyte prepared in Example 1 and the single lithium salt asymmetric structure solid electrolyte prepared in Comparative Example 1; Wherein: a-limiting current density curve; b-lithium deposition|stripping curve; Figure 5 The rate performance and cycle performance of LFP|Li battery; Where: a-rate performance of LFP|Li battery at 25°C; b-cycling performance of LFP|Li battery at 25°C and 1 C rate. DETAILED DESCRIPTION In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] The present invention discloses a method for preparing a double lithium salt asymmetric structure solid electrolyte, comprising the following steps: First, 0.9 g PVDF-HFP, 0.3 g LiFSI, and 0.3 g LiDFOB (mass ratio of 3:1:1) were dissolved in 4.5 mL anhydrous N,N-dimethylformamide (DMF), and then 15 wt% LATP and 30 wt% LATP inorganic fillers were dispersed in two bottles of solution, respectively, to obtain 15 wt% LATP layer and 30 wt% LATP layer precursor solutions; The double-layer electrolyte membrane was prepared by a two-step casting method. A 15wt% LATP precursor solution was cast on a glass plate, coated with a 220 μm scraper, and dried in an oven at 55 °C for 12 h. Then, a 30wt% LATP precursor solution was cast on the 15wt% LATP layer, coated with a 250 μm scraper, and continued to dry in an oven at 55 °C for 24 h to obtain a double lithium salt asymmetric structure solid electrolyte.
[0025] Preferably, two other ratios of double lithium salt solid electrolytes are prepared using mass ratios of 3:1:0.25 and 3:1:0.5, respectively.
[0026] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0027] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0028] Example 1 A method for preparing a double lithium salt asymmetric structure solid electrolyte comprises the following steps: 0.9 g PVDF-HFP, 0.3 g LiFSI, and 0.3 g LiDFOB (mass ratio of 3:1:1) were dissolved in 4.5 mL anhydrous N,N-dimethylformamide (DMF) to obtain a mixed solution; Dispersing 15wt% LATP inorganic filler and 30wt% LATP inorganic filler in two bottles of mixed solution respectively, to obtain 15wt% LATP precursor solution and 30wt% LATP precursor solution respectively; Subsequently, a double-layer electrolyte membrane was prepared by a two-step casting method. A 15wt% LATP precursor solution was cast on a glass plate, coated with a 220 μm scraper, and dried in an oven at 55 °C for 12 h. Then, an inorganic filler with 30wt% LATP was cast on the 15wt% LATP layer, coated with a 250 μm scraper, and continued to dry in an oven at 55 °C for 24 h to obtain a double lithium salt asymmetric structure solid electrolyte.
[0029] Example 2 A method for preparing a double lithium salt asymmetric structure solid electrolyte comprises the following steps: PVDF-HFP, LiFSI, and LiDFOB (mass ratio of 3:1:0.25) were dissolved in 4.5 mL of anhydrous N,N-dimethylformamide (DMF) to obtain a mixed solution; Dispersing 15wt% LATP inorganic filler and 30wt% LATP inorganic filler in two bottles of mixed solution respectively, to obtain 15wt% LATP precursor solution and 30wt% LATP precursor solution respectively; Subsequently, a double-layer electrolyte membrane was prepared by a two-step casting method. A 15wt% LATP precursor solution was cast on a glass plate, coated with a 220 μm scraper, and dried in an oven at 55 °C for 12 h. Then, an inorganic filler with 30wt% LATP was cast on the 15wt% LATP layer, coated with a 250 μm scraper, and continued to dry in an oven at 55 °C for 24 h to obtain a double lithium salt asymmetric structure solid electrolyte.
[0030] Example 3 A method for preparing a double lithium salt asymmetric structure solid electrolyte comprises the following steps: PVDF-HFP, LiFSI, and LiDFOB (mass ratio of 3:1:0.5) were dissolved in 4.5 mL of anhydrous N,N-dimethylformamide (DMF) to obtain a mixed solution; Dispersing 15wt% LATP inorganic filler and 30wt% LATP inorganic filler in two bottles of mixed solution respectively, to obtain 15wt% LATP precursor solution and 30wt% LATP precursor solution respectively; Subsequently, a double-layer electrolyte membrane was prepared by a two-step casting method. A 15wt% LATP precursor solution was cast on a glass plate, coated with a 220 μm scraper, and dried in an oven at 55 °C for 12 h. Then, an inorganic filler with 30wt% LATP was cast on the 15wt% LATP layer, coated with a 250 μm scraper, and continued to dry in an oven at 55 °C for 24 h to obtain a double lithium salt asymmetric structure solid electrolyte.
[0031] Example 4 A method for preparing a double lithium salt asymmetric structure solid electrolyte comprises the following steps: PVDF-HFP, LiFSI, and LiDFOB (mass ratio of 3:1:1) were dissolved in 4.5 mL of anhydrous N,N-dimethylformamide (DMF) to obtain a mixed solution; Dispersing 15wt% LATP inorganic filler and 30wt% LATP inorganic filler in two bottles of mixed solution respectively, to obtain 15wt% LATP precursor solution and 30wt% LATP precursor solution respectively; Subsequently, a double-layer electrolyte membrane was prepared by a two-step casting method. A 15wt% LATP precursor solution was cast on a glass plate, coated with a 220 μm scraper, and dried in an oven at 55°C for 12 h. Then, an inorganic filler with 30wt% LATP was cast on the 15wt% LATP layer, coated with a 250 μm scraper, and continued to dry in an oven at 55°C for 12 h to obtain a double lithium salt asymmetric structure solid electrolyte.
[0032] Example 5 A method for preparing a double lithium salt asymmetric structure solid electrolyte comprises the following steps: PVDF-HFP, LiFSI, and LiDFOB (mass ratio of 3:1:0.5) were dissolved in 4.5 mL of anhydrous N,N-dimethylformamide (DMF) to obtain a mixed solution; Dispersing 15wt% LATP inorganic filler and 30wt% LATP inorganic filler in two bottles of mixed solution respectively, to obtain 15wt% LATP precursor solution and 30wt% LATP precursor solution respectively; Subsequently, a double-layer electrolyte membrane was prepared by a two-step casting method. A 15wt% LATP precursor solution was cast on a glass plate, coated with a 220 μm scraper, and dried in an oven at 55°C for 12 h. Then, an inorganic filler with 30wt% LATP was cast on the 15wt% LATP layer, coated with a 250 μm scraper, and continued to dry in an oven at 55°C for 12 h to obtain a double lithium salt asymmetric structure solid electrolyte.
[0033] Comparative Example 1 A method for preparing a single lithium salt asymmetric structure solid electrolyte comprises the following steps: PVDF-HFP and LiFSI (mass ratio of 3:2) were dissolved in 4.5 mL of anhydrous N,N-dimethylformamide (DMF) to obtain a mixed solution; Dispersing 15wt% LATP inorganic filler and 30wt% LATP inorganic filler in two bottles of mixed solution respectively, to obtain 15wt% LATP precursor solution and 30wt% LATP precursor solution respectively; Subsequently, a double-layer electrolyte membrane was prepared by a two-step casting method. A 15wt% LATP precursor solution was cast on a glass plate, coated with a 220 μm scraper, and dried in an oven at 55 °C for 12 h. Then, an inorganic filler with 30wt% LATP was cast on the 15wt% LATP layer, coated with a 250 μm scraper, and continued to dry in an oven at 55 °C for 24 h to obtain a single lithium salt asymmetric structure solid electrolyte.
[0034] Linear sweep voltammetry (LSV) was used to test the electrochemical window size of different electrolytes and explore the effect of LiDFOB content on the electrochemical stability of solid electrolytes. Figure 1 As shown, Figure 1 (a) shows that after adding LiDFOB (m PVDF-HFP:LiFSI: LiDFOB =3:1:0.25), the oxidation voltage of the solid electrolyte increased from 4.13 V of the single lithium salt to 4.63 V; then the content of LiDFOB was increased, the oxidation voltage increased from 4.75 V (3:1:0.5) to 4.84 V (3:1:1), and the electrochemical window was significantly improved, indicating that the double lithium salt asymmetric structure solid electrolyte can stably exist without decomposition in a wider voltage range, which is conducive to the operation of SSLMBs at high voltage. The subsequent tests were all carried out with a mass ratio of PVDF-HFP:LiFSI: LiDFOB=3:1:1; the critical current density (CCD) of the double lithium salt asymmetric structure solid electrolyte can reach 1.25 mA cm −2 ( Figure 1 b), indicating that solid-state lithium metal batteries can operate at high current density, and lithium ions can be quickly transported at the interface between the electrode and the electrolyte, which helps to achieve fast charging and discharging; the Nyquist diagram of electrochemical impedance is shown in Figure 1 As shown in (c), at 25 °C, the impedance R of the double lithium salt asymmetric solid electrolyte is 4.94 Ω and the ionic conductivity is 5.58×10 −4 S cm −1 , which is significantly higher than that of single lithium salt solid electrolyte (ionic conductivity is 2.21×10 −4 S cm−1 , R=13.40Ω).
[0035] Figure 2 From the surface and cross-sectional morphologies of the double lithium salt asymmetric structure solid electrolyte and the single lithium salt asymmetric structure solid electrolyte prepared in Comparative Example 1, an obvious layered asymmetric structure can be observed. From the SEM image of the electrolyte membrane surface, it can be seen that the LATP ceramic particles are uniformly dispersed in the polymer matrix, and the 30wt% LATP layer has a significantly higher ceramic content than the 15wt% LATP layer. These morphological features indicate that a double-layer asymmetric solid electrolyte has been successfully constructed. The thicknesses of the single lithium salt and double lithium salt solid electrolyte membranes are 58 μm and 54 μm, respectively.
[0036] like Figure 3 As shown, the lithium ion migration number of the double lithium salt asymmetric structure solid electrolyte prepared in Example 1 and the single lithium salt asymmetric structure solid electrolyte prepared in Comparative Example 1 were tested. + The migration number (0.51) is significantly better than that of single lithium salt electrolyte (0.25), and the high Li + The migration number helps to alleviate the interface polarization and improve the fast charging capability of SSLMBs.
[0037] Figure 4 The limiting current density curve and lithium deposition|stripping curve of the double lithium salt asymmetric structure solid electrolyte prepared in Example 1 and the single lithium salt asymmetric structure solid electrolyte prepared in Comparative Example 1 are as follows: Figure 4 As shown in (a), the dual lithium salt electrolyte membrane has a high limiting current density (9.99 mA cm −2 ), the high limiting current density indicates that the electrolyte can effectively inhibit the growth of lithium dendrites, thereby improving the safety of the battery. Assembling lithium symmetric batteries verified the stability of the solid electrolyte on the lithium metal anode ( Figure 4 b); at 0.3 mA cm −2 At a current density of , the Li|single lithium salt|Li battery produces a high overpotential and the battery short-circuits quickly, while the Li|double lithium salt|Li battery exhibits a lower overpotential and can operate stably for more than 550 h, indicating that the double lithium salt electrolyte has better stability to lithium metal.
[0038] The electrochemical performance of LFP|Li battery was tested at 25 ℃. LFP|Dual lithium salt|Li battery showed excellent rate performance ( Figure 5 a) At 0.1, 0.2, 0.5, and 1.0 C rates, the battery can deliver 156.95, 153.61, 143.41, and 128.28 mAh g −1The discharge capacity of the two SSLMBs was 2.34 W / m2 / cm2. In contrast, the LFP|single lithium salt|Li battery could not provide sufficient discharge capacity. The long-term cycling stability of the two SSLMBs was further compared ( Figure 5 b) After 140 cycles at 1 C, the LFP|dual lithium salt|Li battery can still provide 118.57 mAh g −1 The discharge specific capacity of the LFP|single lithium salt|Li battery was 85.23 mAh g after 140 cycles, with a capacity retention rate of 89.44% and an average coulombic efficiency of more than 99%. −1 The discharge specific capacity of LFP|double lithium salt|Li battery has a capacity retention rate of 64.29%. This is because LiDFOB helps to form a stable cathode electrolyte interface (CEI) and enhances the interfacial compatibility with the cathode, making the LFP|double lithium salt|Li battery show better rate performance and cycle performance.
[0039] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a double lithium salt asymmetric structure solid electrolyte, characterized in that: The following steps are involved: Dissolving PVDF-HFP, LiFSI and LiDFOB in a solvent to obtain a mixed solution; Dispersing LATP inorganic fillers in the mixed solution respectively to obtain two LATP precursor solutions with different concentrations; Two LATP layer precursor solutions with different concentrations were prepared by a two-step tape casting method to obtain a double lithium salt asymmetric structure solid electrolyte.
2. The method for preparing a double lithium salt asymmetric structure solid electrolyte according to claim 1, characterized in that: The usage ratio of the PVDF-HFP, LiFSI, LiDFOB and solvent is 3 g:1 g:(0.25-1) g:15 mL.
3. The method for preparing a double lithium salt asymmetric structure solid electrolyte according to claim 1, characterized in that: The solvent is N,N-dimethylformamide.
4. The method for preparing a double lithium salt asymmetric structure solid electrolyte according to claim 1, characterized in that: The concentrations of the two LATP precursor solutions of different concentrations are respectively a high-concentration LATP precursor solution and a low-concentration LATP precursor solution; The concentration of the high-concentration LATP precursor solution is 30 wt %, and the concentration of the low-concentration LATP precursor solution is 15 wt %.
5. The method for preparing a double lithium salt asymmetric structure solid electrolyte according to claim 4, characterized in that: The preparation process of the double lithium salt asymmetric structure solid electrolyte is prepared by a two-step tape casting method using two different concentrations of LATP layer precursor solutions as follows: A low-concentration LATP precursor solution is first cast on a substrate, coated with a scraper, and then dried. A high-concentration LATP precursor solution is then cast, coated with a scraper, and then dried to obtain a double lithium salt asymmetric structure solid electrolyte.
6. The method for preparing a double lithium salt asymmetric structure solid electrolyte according to claim 5, characterized in that: When the scraper is used to scrape a small concentration of LATP precursor solution, the thickness of the scraper is 220 μm; When the scraper is used to scrape a high-concentration LATP precursor solution, the thickness of the scraper is 250 μm; The substrate is a glass plate.
7. The method for preparing a double lithium salt asymmetric structure solid electrolyte according to claim 5, characterized in that: The temperature for drying the small concentration LATP precursor solution after scraping is 55 °C and the time is 12~24 h.
8. The method for preparing a double lithium salt asymmetric structure solid electrolyte according to claim 5, characterized in that: The temperature for drying the high-concentration LATP precursor solution after scraping is 55°C and the time is 12 to 24 hours.
9. A double lithium salt asymmetric structure solid electrolyte, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the double lithium salt asymmetric structure solid electrolyte according to claim 9 in a solid-state lithium metal battery.